2014
DOI: 10.7567/jjap.53.094001
|View full text |Cite
|
Sign up to set email alerts
|

Drain-induced Schottky barrier source-side hot carriers and its application to program local bits of nanowire charge-trapping memories

Abstract: A fiber-bulk hybrid Er:YAG laser with the 1617 nm single frequency (SF) laser output is reported. The pump source was a 1532 nm Er,Yb fiber laser. Two intra-cavity etalons were used to obtain the SF operation at 1617 nm. Up to 640 mW SF output at 1617 nm was obtained, with a slope efficiency of 36.02%. 1532 nm fiber laser Fiber L1 L2 Input mirror Uncoated etalon Er:YAG Coated etalon Output coupler 1617 nm output

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The Fermi level unpinning enables easy modulation of the Schottky barrier, a feature that can be exploited to tune Gr/Si devices to match specific performance requests 11,56 . Deviations from the Schottky-Mott prediction are mainly due to image force lowering 57 or hot electrons barrier lowering [58][59] .…”
Section: Fig 3cmentioning
confidence: 84%
See 1 more Smart Citation
“…The Fermi level unpinning enables easy modulation of the Schottky barrier, a feature that can be exploited to tune Gr/Si devices to match specific performance requests 11,56 . Deviations from the Schottky-Mott prediction are mainly due to image force lowering 57 or hot electrons barrier lowering [58][59] .…”
Section: Fig 3cmentioning
confidence: 84%
“…Another important effect which can lead to a stronger V-dependence of the reverse current is the Schottky barrier lowering caused by hot electrons [58][59] that might originate even a quadratic ΔΦ B (V). In this scenario, the gating effect induces abrupt band bending around the Schottky barrier that increases the lateral field, which in turn produces significant enhancement of hot carriers.…”
Section: 𝑘𝑇mentioning
confidence: 99%
“…To accomplish this the memory retention time needs to be significantly increased. This could be done both using nonvolatile NW based designs [49][50][51] or more traditional Si charge trapping devices that can be connected to the NWs [52,53]. As the memory is only included in the artificial neurons, this construction potentially using a standard chip platform is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 8 believed that the image force also can lower SBH, which will result in some unreasonable conclusions shown in the following content. Chang et al 25 experimentally reported that the SBH lowering is caused by hot electrons for Schottky barrier nanowire charge-trapping silicon–oxide–nitride–oxide–silicon devices. It implies that the physical origin of the SBH lowering in field-effect transistors caused by hot electrons should carefully be considered.…”
mentioning
confidence: 99%